Effect of Solvents and Crystallization Methods on the Formation of Carbamazepine-Saccharin Co-Crystal - Ab Rahman, Fatinah; N. Engku Mat Nasir, Engku; Abd Rahim, Syarifah; Z. Edros, Raihana; Anuar, Nornizar (International Journal of Engineering and Technology, 2018)
Active Pharmaceutical Ingredients (API) crystallized in its co-crystal form is believed to be able to improve the physicochemical properties of its pure crystal. Carbamazepine (CBZ) and saccharin (SAC) were used in this study in investigation of effect of solvents and crystallization methods on the formation of CBZ-SAC co-crystal. There were four different solvents (acetonitrile, ethanol, ethyl acetate and propanol) and two crystallization methods (slurry and stirring crystallization) used in this study. The crystals produced were characterized by Differential Scanning Calorimetry (DSC), Powder X-Ray Diffraction (PXRD), Fourier Transform Infrared (FTIR) and optical microscopy. The findings revealed that only Form I of CBZ-SAC co-crystals was successfully formed for all parameters under studied. It was concluded that the type of solvents, crystallization methods and CBZ:SAC ratio used in this study did not play an important role on the CBZ-SAC Form I co-crystal formation for this system.Â Â Â